Relationship Between Knowledge and Community Attitudes in Preventing Leptospirosis - Maharani Suci Wulandari; Elza Anggraeni Trisnawati; Achmad Husen; Hilwatut Taqiyah; Siti Nur Hasina (GLOBAL HEALTH SCIENCE GROUP, 2024)
Leptospirosis is a zoonotic (animal-to-human transmission) disease caused by Leptospira bacteria that has flu-like symptoms. This disease has a major impact on health, especially in sub-tropical and tropical countries. The main reservoir of this disease is rats. This study aims to determine the relationship between knowledge and community attitudes in preventing Leptospirosis in Sumberrejo village, RT 03 RW 02, Pakal, Surabaya. Method: using quantitative method with cross sectional study design. The population in this study was the community of Sumberrejo RT03, RW02, Pakal, Surabaya, which amounted to 85 people. Samples were taken using purposive sampling technique in accordance with the inclusion and exclusion criteria totaling 70 people. The measuring instrument used was a knowledge and attitude questionnaire. Results: 37 (52.9%) knowledge, 51 (72.9%) attitude, p-value < α which is 0.001. Conclusion: Based on the variables, most people have knowledge of Leptospirosis in the low category as many as 37 (52.9%), for the attitude of the community most of the attitude is bad as many as 51 (72.9%), the correlation coefficient value is 0.420 which shows a positive correlation direction. This shows that there is a relationship between knowledge and community attitudes in preventing Leptospirosis. Suggestion: Socialization of both material exposure and the application of clean and healthy living behavior is needed, so that people can increase awareness of the dangers if exposed to Leptospirosis.